The US$ 2.1 billion derivative loss that ruined the Brazilian Aracruz. (2017) - Murcia, Fernando Dal-Ri; Murcia, FlÁ¡via Cruz De Souza; Pfitscher, Elisete Dahmer
This paper critically analyses the case of the Brazil-based Aracruz Celulose S.A., which was one of the world's largest producer of bleached eucalyptus pulp. In 2008, it posted a derivate loss of US$ 2.1 billion dollars, which is considered the 7th largest derivative loss for all time. For these, we use publicly available information about the case that includes: 1) financial statements; 2) notices of material events announced at the Securities Exchange Commission (SEC) and in the Comissão de Valores Mobiliários (Brazilian Exchange Commission); 3) the administrative proceeding process conducted by Comissão de Valores Mobiliários; 4) the company's website; 5) newspaper and website articles; 6) academic journals. Just before the crisis, Aracruz was a very successful company and its financial structure was solid. That loss caused a huge solvency problem that lead to end of the company. Aracruz went from being a history of success to a situation of financial insolvency. Our analysis evidences that Aracruz was operating as a 'bank', using derivatives to speculate against the US dollar and not really to hedge its revenues, as it was heavily leveraged. The results show the misuse of derivatives can damage a company and even lead to bankruptcy.